Studies on Baits for Lobsters - K.V., Mohan Rajan; B., Meenakumari; M., Shahul Hameed (Fishery Technology, 2025)
Baits constitute an important component and represent a major expense in trap fishing for spiny lobsters. Fishing experiments were carried out with five kinds of baits namely mussel, sea urchin, cattle hocks, animal guts and diesel oil, in order to assess their efficacy in attracting lobsters. 61.2% of total catch was landed by using mussel as bait followed by diesel oil (27.7%), sea urchins (9.3%) and cattle hocks (1.7%), while animal gut was ineffective. Though mussel was the best among baits tried, in places where they are not available, diesel oil could prove to be a cheap alternative bait for lobsters.